Prevalence of depressive disorders among pregnant women in Brazil in 2019: A descriptive cross-sectional study - Maira Gonçalves de Oliveira Lucas; Maria Isabel do Nascimento (São Paulo Medical Journal)
ABSTRACT BACKGROUND: Prenatal depression threatens maternal and child well-being and interferes with issues prioritized by the 2030 agenda for the Sustainable Development Goals. OBJECTIVES: This study aimed to estimate the prevalence of depressive disorders during pregnancy using the Patient Health Questionnaire-9 (PHQ-9). DESIGN AND SETTING: A cross-sectional study using a sample of pregnant Brazilian women, representative of Brazil as a whole. METHODS: Data were obtained from the National Health Survey 2019 (PNS-2019), as coordinated by the Instituto Brasileiro de Geografia e Estatística (IBGE). Women aged 18-49 years who were pregnant during PNS-2019 data collection were included. The prevalence of depressive disorders and 95% confidence intervals (95%CI) were calculated. RESULTS: The prevalence of depression before the current pregnancy was 6.03% (95%CI: 3.80%; 8.25%). Using the PHQ-9, the prevalence of Major Depressive Disorder (MDD) in the current pregnancy was estimated to be 17.39% (95%CI: 12.70%–22.06%) among pregnant women who were targeted by the PNS-2019. Moreover, MDD was 15.26% (95%CI: 10.54%; 19.97%) among those who were free from depression history and in half of the pregnant woman population with depression history. Suicidal ideation has been reported in almost 23% of pregnant women with a history of depression. The two items from Patient Health Questionnaire-2 (PHQ-2) (anhedonia and depressed mood) with a cutoff of ≥ 3 presented similar results. CONCLUSIONS: Depression during pregnancy affects a non-negligible proportion of pregnant women, thus constituting an important public health problem. Therefore, it is crucial to discuss the implementation of regular screening for depression during prenatal care programs in Brazil.